New approach to assess forest fragmentation based on multiscale similarity index - Pawel Netzel; Luiza Tyminska; Debebe Dana Feleha; Jaroslaw Socha (Ecological Indicators, 2024)
Forest fragmentation is a landscape-level process. After fragmentation, a larger forest area is changed into smaller, mostly isolated, and geometrically complex patches. Proper assessment of forest fragmentation requires addressing key aspects, including the continuous forest's size and shape, the integrity of the forest, and the interpatch spatial distance distribution of forest patches that are separated by nonforest land.The article presents a new approach to assessing the fragmentation of forests in a given area based on the similarity of a forested area's pattern to a pattern of a fully forested area. Jensen--Shannon similarity is used to create a measure of forest fragmentation. The proposed approach allows both the calculation of forest fragmentation at a given scale and the calculation of a multiscale fragmentation assessment as a single index. In addition, the proposed fragmentation index can be used to identify forest complexes better and assess their fragmentation.This approach is flexible, and applying it to other spatial phenomena, such as calculating multiscale fragmentation of urban or agricultural areas, is possible. The article presents the results of applying the proposed method to a test forest-covered region and to an area of the entire country (Poland). The calculations were made with a spatial resolution of 10 m. Moreover, we compared the results of the method to the FAD-APP index. The results show benefit of applying the proposed indicator to forested areas.